2019
DOI: 10.1021/acsnano.8b06924
|View full text |Cite
|
Sign up to set email alerts
|

Golgi Apparatus-Targeted Chondroitin-Modified Nanomicelles Suppress Hepatic Stellate Cell Activation for the Management of Liver Fibrosis

Abstract: Liver fibrosis is a serious liver disease associated with high morbidity and mortality. The activation of hepatic stellate cells (HSCs) and the overproduction of extracellular matrix proteins are key features during disease progression. In this work, chondroitin sulfate nanomicelles (CSmicelles) were developed as a delivery system targeting HSCs for the treatment of liver fibrosis. CS-deoxycholic acid conjugates (CS–DOCA) were synthesized via amide bond formation. Next, retinoic acid (RA) and doxorubicin (DOX)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 67 publications
10
68
0
Order By: Relevance
“…In addition, the production and liberation of TNF-α are predominantly regulated by the TLR4/NF-κB signaling pathway during liver inflammation (37). Accordingly, the inhibition of the TLR4/NF-κB signaling pathway can decrease TNF-α production, which is an effective strategy for FHF alleviation (38,39). In our study, MF suppressed TNF-α synthesis transcriptionally and translationally, as shown by the decrease in mRNA and protein of TNF-α after MF pretreatment in both mice and KCs.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, the production and liberation of TNF-α are predominantly regulated by the TLR4/NF-κB signaling pathway during liver inflammation (37). Accordingly, the inhibition of the TLR4/NF-κB signaling pathway can decrease TNF-α production, which is an effective strategy for FHF alleviation (38,39). In our study, MF suppressed TNF-α synthesis transcriptionally and translationally, as shown by the decrease in mRNA and protein of TNF-α after MF pretreatment in both mice and KCs.…”
Section: Discussionsupporting
confidence: 52%
“…There have been a variety of experimental studies conducted targeting the ECM by different means to interfere with hepatic fibrosis. Chondroitin sulfate deoxycholic acid conjugates loaded with retinoic acid and doxorubicin were found accumulated within the Golgi apparatus and destroyed the production of collagen (70). Relaxin administration in well-established liver fibrosis model has shown to reduce collagen expression, α-SMA levels, and lowering liver enzymes (71).…”
Section: Reversal Of Fibrosis By Targeting the Extracellular Matrix: Novel Targets And Formulation-based Approachesmentioning
confidence: 99%
“…103 Gong's team repeatedly proved that chondroitin sulfate (CS) nanomicelles targeted the Golgi since the glycosyltransferases in the Golgi could specifically bind to CS. 104,105 However, it should be pointed out that compared with the targeting of the mitochondria and nuclei, the subcellular targeting of the ER and Golgi is still in its infancy, with not enough information available to apply comprehensive design strategies.…”
Section: Er and Golgi Targeting Nanoformulationsmentioning
confidence: 99%